Knowledge and Technologies’ assimilation and transference in the linking among University - Local Government - Population: Case Lacabamba - Lovera, Daniel (2007)
The Universidad Nacional Mayor de San Marcos and its Research Institute IIGEO, through fulfilling their vision, mission and social responsibility, are co-relating institutional efforts with local governments through framework and specific agreements, such as in the case of the Municipality of Lacabamba. Through this article we show how the sharing research of a multidisciplinary and local population team allowed the carrying out of the agreed strategic planning, the identification of the projects portfolio, citizen’s consultancy, participative budget, projects profile, local participants’ capacities strengthening, among several other deliverable items. The “Adaptation of a waste waters treatment system in the Urban Community of Lacabamba, Ancash Region, Peru, through the use of artificial Damp Areas Technologies” project was particularly planned anperformed. This project allowed the transfering of technology for the treatment of domestic waters, the installation of a communal orchard with waters having been treated out of artificial damp areas, and the pre-active training of sharecroppers, teachers, students and women, these all lately having being motivated and having therefore set their homemade orchards. This multidisciplinary intervention has allowed the beginning of an encouraged long-life research upon the resources in the Yanacancha-Cucullo and Chonta archaeological complex, so as to position them among a suitable heritage worth and identity with the purpose of improving the population’s life quality.